2001
DOI: 10.1038/nsb0901-770
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The pathogenesis of transmissible encephalopathies is associated with the conversion of the cellular prion protein, PrP(C), into a conformationally altered oligomeric form, PrP(Sc). Here we report the crystal structure of the human prion protein in dimer form at 2 A resolution. The dimer results from the three-dimensional swapping of the C-terminal helix 3 and rearrangement of the disulfide bond. An interchain two-stranded antiparallel beta-sheet is formed at the dimer interface by residues that are located in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
191
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 475 publications
(198 citation statements)
references
References 30 publications
6
191
0
Order By: Relevance
“…The lack of stability of helical conformation within helix II fits with a previously proposed model for PrP Sc formation (39), where dimerization and domain swapping involving this region of PrP occur early in the process. However, whereas the crystal structure of the ␣-helical domain-swapped dimer of PrP can be accommodated in ␤-PrP fibril subunits, the lack of significant ␣-helicity observed in the far-UV CD spectra of ␤-PrP oligomers and fibrils is inconsistent with this conformation constituting the fibril subunits (40).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The lack of stability of helical conformation within helix II fits with a previously proposed model for PrP Sc formation (39), where dimerization and domain swapping involving this region of PrP occur early in the process. However, whereas the crystal structure of the ␣-helical domain-swapped dimer of PrP can be accommodated in ␤-PrP fibril subunits, the lack of significant ␣-helicity observed in the far-UV CD spectra of ␤-PrP oligomers and fibrils is inconsistent with this conformation constituting the fibril subunits (40).…”
Section: Discussionsupporting
confidence: 50%
“…4). This region of the protein provides the hinge in a three-dimensional domain-swapped dimer of human PrP (39), and appears to undergo a marked conformational change in ovine PrP Sc (66), suggesting a possible role for this region of the protein in the conformational change to PrP Sc . It is also interesting to observe that the residues immediately preceding helix I show similar upfield CЈ chemical shifts.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that oligomerization of PrP can occur through the formation of intermolecular disulfide bonds (50,51). However, oligomers of mPrP-(121-231) were not disassembled even by boiling in the presence of 140 mM dithiothreitol and SDS (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…A simple observation that emerges from the examination of the structures of all mammalian recombinant PrPs 1 that have been solved so far in their ␣-helix-rich forms is that they have a highly positively charged N-terminal tail that is flexibly disordered and a stable globular C-terminal domain (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). It is becoming clear that these structural features must have some functional significance.…”
mentioning
confidence: 99%